Geophysical evidence for thrust faulting in the Carboniferous Antigonish-Mabou Subbasin, Nova Scotia - Durling, P.; Harvey, P.; Howells, K. (Atlantic Geology, 1995)
Petroleum industry seismic reflection data and gravity profiles were used to interpret offshore and onshore geological structures in the Carboniferous Antigonish-Mabou Subbasin. Four seismic horizons were mapped, and the deepest (reflection 'A'; near the base of the Windsor Group) was contoured to produce a time-structure map of the subbasin. The Antigonish-Mabou Subbasin is structurally complex and deepens to 2.8 s two-way time (S600 m) in the north-central part of St. Georges Bay. It is substantially thinner onshore in the Antigonish (up to 1.0 s; 2000 m) and Mabou areas (up to 1.6 s; 3200 m). The geophysical data have revealed more complex structures at depth than previously shown by surface mapping, boreholes or shallow penetration marine seismic profiling data. Within the subbasin, low angle thrusts and high angle strike-slip faults, salt structures and elevated basement blocks were mapped. Some faults have large throws (up to 3200 m) and separate large uplifted basement blocks from deeper basinal areas. Movement on the faults is of post Windsor age. New evidence for thrusting is provided by: seismic data in southern St. Georges Bay; onshore seismic profiles in the Mull River area; and gravity profiles near Antigonish. Only one of these thrust faults has been mapped at the surface by previous workers in the area. The thrust faults place Windsor Group and older rocks over basal Windsor Group reflections (reflection 'A'). The thrust faults appear to terminate in the Windsor Group, where movement on the thrusts is transferred to back-thrusts and/or transformed into disharmonic folding above a decollement within the Windsor Group evaporites.